The Influence Model Contextual Teaching and Learning Component Community on Social Skills of Elementary School Students - Mulyani, Srie; Wahyudin, D.; Caturiasari, Jennyta; Yogiarni, Tiara; Fajrussalam, Hisny (CV. Creative Tugu Pena, 2023)
Social skills abilities in society are very necessary to prepare good and educated citizens. Social skills need to be developed in learning through models, methods, approaches or learning techniques, especially in social studies learning. To determine the influence of the Community Component Contextual Teaching and Learning model in efforts to improve social skills abilities, as well as determine the increase in the final score of students' social skills abilities, the researchers used a quasi experiment (quasi experiment). The subjects in this study consisted of 48 fifth grade elementary school students. The results of data analysis show that the influence of the CTL model on students' social skills is 49.6%. The results of the n-gain t test obtained a sig value of 0.000, so H0 rejected so it can be concluded that the increase in social skills abilities of students who receive CTL model learning is better than students who receive conventional learning. Keywords: Contextual Teaching and Learning (CTL) Model, Learning Community, Student Social Skills